Phylogenetic analyses, morphological characteristics, and host specificity reveal Anthracoidea koopmanii sp. nov. (Anthracoideaceae, Ustilaginales) on Carex oreophila (Cyperaceae) from Armenia - Denchev, Teodor T.; Denchev, Cvetomir M.; Więcław, Helena; Mišek, Vojtěch; Kemler, Martin (Phytotaxa, 2026)
Anthracoidea species are highly specialized parasitic fungi on Carex. Their host range is restricted to a single sedge species or sedge species belonging to the same or closely related sections. The present study reports for the first time the finding of an Anthracoidea species on sedge in Carex sect. Capituligerae, based on a recent collection from Armenia. We employed an integrative systematic approach combining molecular (based on LSU rDNA sequences) and morphological data with host-specificity to elucidate the taxonomic status of this Anthracoidea species. The phylogenetic analyses indicate that it differs from the Anthracoidea species with available molecular data. Additionally, this species possesses morphological characters, by which it can be easily distinguished from all Anthracoidea species recognized on sedges in the former Capitata Clade sensu Roalson et al. It differs from Anthracoidea obtusatae on Carex obtusata by its larger spores and lack of internal swellings, from A. rupestris on Carex rupestris by its thinner spore walls and lack of protuberances, internal swellings, and light refractive areas, from A. nardinae on Carex nardina by having punctate to minutely verruculose spore wall ornamentation (as seen in SEM), and from the other Anthracoidea species by specialization on Carex oreophila. Based on molecular and morphological evidence, and host specialization, a new species, Anthracoidea koopmanii, is described and illustrated. The phylogenetic placement and affinities of the new species in Anthracoidea are analyzed.